Exploring Spanish writing abilities of children with developmental language disorder in expository texts - Balboa-Castells, Raquel; Ahufinger, Nadia; Sanz-Torrent, Mònica; Andreu, Llorenç (Frontiers in Psychology, 2024)
Numerous studies have shown that children with developmental language disorder (DLD), in addition to oral language difficulties, exhibit impaired writing abilities. Their texts contain problems in grammar, organisation, cohesion, and length of written output. However, most of these studies have been conducted with English speakers. English is characterised by complex phonological structure, opaque orthography, poor morphology and strict word order. The aim of this research is to observe the writing abilities of children with DLD in a language with simple phonological structure, transparent orthography, rich morphology and flexible word order like Spanish in the production of expository texts. Twenty-six children with DLD (mean age in months = 128.85) and 26 age-and sexmatched typically developing (TD) children (mean age in months = 124.61) wrote an expository text about their favourite animal. In order to analyse how the two groups plan and encode written texts, we looked at word frequency and sentence structure, grammatical complexity and lexical density, and omissions and errors. Compared to the TD group, the children with DLD omitted more content words; made more errors with functional words, verb conjugation and inflectional morphemes, and made a large number of spelling errors. Moreover, they wrote fewer words, fewer sentences, and less structurally and lexically complex texts. These results show that children with DLD who speak a transparent orthography language such as Spanish also have difficulties in most language areas when producing written texts. Our findings should be considered when planning and designing interventions.